UiTM College Vehicle Registration System (i-CVeR) / Nur Azlin Nur Hamidi - Nur Hamidi, Nur Azlin (2017)
Vehicle is becoming a human basic need in current trend thus the registration and permit are highly required for record and regulations. In most local universities, the process of vehicle registration is done manually where residents will be needed to register their vehicle or at least apply for vehicle sticker to get a permit. As in UiTM Dungun, the process of getting the sticker involves several processes which takes some times as college resident will be needed to verify their qualification and certification as well as undergo three steps to get approved. Hence, UiTM College Vehicle Registration System (i-CVeR) was proposed and developed to encounter the current problem. The system eventually help the student to register their vehicle and to get a parking space while this system also help the college management in managing and to keep track records for all the vehicle and parking. Adapted Waterfall Model is used in developing i-CVeR. There are four phases in the model starting with requirement analysis, system design, implementation and system testing. Once the system is completed, functionality testing was conducted by the developer and tester based on stated requirements. Three (3) experts and 30 respondents involve in evaluation the usability of i-CVeR. There were 6 constructs in the evaluation process used for both expert and user; interface, usefulness, consistency, user experience, usability and satisfaction. The result shows that majority of the respondents choose user experience construct as the highest mean (Mean=4.22 and SD=0.66). In order to improve the system, few enhancements are needed such as the system should be upgraded as a responsive web to enable the users to view it in all devices such as mobile, tablet and PC and the student can bid and select parking based on their roles and availability.